Can Multispectral Dermoscopy Help In Distinguishing Blue Color? - Janssen, Laudine; Van Kelst, Sofie; Diricx, Bart; Kimpe, Tom; Papeleu, Jorien; Verhaeghe, Evelien; Brochez, Lieve; Garmyn, Marjan (Dermatology Practical & Conceptual, 2023)
Introduction: The interpretation of colors is essential in the dermoscopic evaluation of skin lesions. The same blue color on white dermoscopy may indicate blood or pigment deep in the dermis. Skin parameter maps, generated from multispectral dermoscopic images, allow to more clearly visualize specific skin structures such as pigment distribution (pigment map) and vasculature (blood map).Objectives: Aim of this research is to investigate whether skin parameter maps can be used to objectively identify and distinguish the presence of pigment and blood.Methods: We retrospectively analyzed 24 blue naevi and 79 angiomas. The skin parameter maps of each of the lesions were independently reviewed by 3 expert dermoscopists, in the absence of the regular white-light dermoscopic image.Results: All the observers provided high levels of diagnostic accuracy for blue naevus and angioma based on skin parameter maps alone, and the dermoscopic diagnosis was considered substantially reliable because of the 79% of diagnostic K agreement. Percentages of blue naevi and angiomas that showed respectively deep pigment and blood were very high at 95.8% and 97.5%. There was a percentage of lesions that counterintuitively showed blood in blue naevi (37.5%) and deep pigment in angiomas (28.8%).Conclusions: Skin parameter maps based on multispectral images can help to objectify the presence of deep pigment or blood in blue naevi and angiomas. Application of these skin parameter maps could help in the differential diagnosis between pigmented and vascular lesions.